Efficiency analysis of the 25 kV/50 Hz traction network with static frequency converters - Mlynařík, Ladislav; Hebelka, Vlastimil; Novák, Jaroslav; Sadílek, Ondřej; Lettl, Jiří (IEEE (Institute of Electrical and Electronics Engineers), 2023)
Based on computer simulations, the article shows possible energy savings when is railway line 25kV/50Hz powered from indirect static frequency converters instead of the conventional power supply only by transformers. One operational situation including 37 trains is sequentially powered by seven different combinations of conventional and converter power stations. Simulations based on the compiled mathematical equations show the changing energy at the input to the power stations depending on their types and the setting of the output control characteristics.
Analýza účinnosti trakční sítě 25 kV/50 Hz se statickými frekvenčními měniči
Keywords: Converters for Special Applications, Railway Power Stations, Simulation of Traction Grid; Měniče pro speciální aplikace, železniční napájecí stanice, simulace trakční sítě